1989
DOI: 10.1002/cne.902790310
|View full text |Cite
|
Sign up to set email alerts
|

Topographical organization of the projections from the reticular thalamic nucleus to the intralaminar and medial thalamic nuclei in the cat

Abstract: The topography of the projections from the reticular nucleus of the thalamus (RT) to the intralaminar and medial thalamic nuclei were studied in the cat by the method of retrograde transport of horseradish peroxidase (HRP). Single small injections of the enzyme were made in the different intralaminar nuclei--mediodorsal, ventromedial, midline, and habenular--and in anterior group nuclei. The location and density of the neuronal labeling in the different parts of the RT were studied in each case. Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 34 publications
3
32
1
Order By: Relevance
“…These findings are in good agreement with the results of studies in the rat and cat Velayos et al, 1989;Lozsadi, 1995;Gonzalo-Ruiz and Lieberman, 1995;Kolmac and Mitrofanis, 1997) that also described connections of the anterior pole with a variety of a,c,f), the symmetric nature of the synapse with some underlying dense substance is clearly seen. In b, e, and f note also Puncta aedherentia to the right from synaptic contacts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in good agreement with the results of studies in the rat and cat Velayos et al, 1989;Lozsadi, 1995;Gonzalo-Ruiz and Lieberman, 1995;Kolmac and Mitrofanis, 1997) that also described connections of the anterior pole with a variety of a,c,f), the symmetric nature of the synapse with some underlying dense substance is clearly seen. In b, e, and f note also Puncta aedherentia to the right from synaptic contacts.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is not clear whether this concept can be extrapolated to all NRT sectors, specifically those related to the motor, limbic, association, and intralaminar nuclei connected with the frontal lobe. Based on retrograde tracing studies in cats and rats, it has been suggested that the rostral NRT sector or anterior pole as it is also known, is organized differently from the sensory sectors: it is connected with a large number of thalamic nuclei, including intralaminar, midline, and limbic without precise topography (Velayos et al, 1989;Gonzalo-Ruiz and Lieberman, 1995;Lozsadi, 1995;Kolmac and Mitrofanis, 1997;Lizier et al, 1997). Recent anterograde tracing studies (Yi et al, 1993;Kultas-Ilinsky et al, 1995;Tai et al, 1995) have further confirmed the connections of the anterior sector of the NRT with the same nuclei in the rhesus monkey as well.…”
mentioning
confidence: 99%
“…Anterograde labeling is faint in VM-VL. Terminallike labeling is visible in the anterodorsal zone of the pregeniculate sector (Velayos et al, 1989) of the reticular thalamic nucleus. Thereon, labeled axons can be followed medially and caudally as they traverse the ventral thalamic complex en route to PoM and LM, arranged in conspicuous small bundles.…”
Section: Labeling In the Thalamus After Cortical Injectionsmentioning
confidence: 98%
“…Interestingly, the bundle of axons directed to the thalamus and other subcortical structures follows a route ventral to the putamen into the sublenticular portion of the internal capsule, whereas after injections in the other areas of the orbitosylvian region these fibers always follow a dorsal route into the main, dorsal portion of the internal capsule. When passing through the most caudal part of the infrageniculate sector (Velayos et al, 1989) of the reticular thalamic nucleus, labeled axons leave terminal-like labeling. Thereon, axons travel within the acoustic radiation toward the caudal pole of the medial geniculate complex.…”
Section: Labeling In the Thalamus After Cortical Injectionsmentioning
confidence: 99%
“…As a result of this disfacilitation, thalamic neurons would become sufficiently hyperpolarized to change their firing mode from tonic to phasic, as occurs in the transition to SWS (Steriade et al, 1994). Moreover, the thalamic reticularis neurons, which contain GABA (Houser et al, 1980) and project onto thalamic relay neurons, including midline, medial, and intralaminar nuclei of the diffuse thalamocortical projection system Jones, 1985;Velayos et al, 1989), would begin to burst, hyperpolarizing the thalamocortical neurons and entraining them first in a spindle and then ␦ rhythmicity (von Krosigk et al, 1993;Steriade et al, 1994). Thalamic neurons also oscillate in a slower rhythm with long-lasting hyperpolarizations in association with the "slow oscillation" on the cortex (Ͻ1 Hz) (Contreras et al, 1996), a recently described sleep rhythm (Steriade et al, 1994) that was not measured in the present study.…”
Section: Negative Covariation Of Rcbf With ␦ Ormentioning
confidence: 99%